Enhanced Piezoelectric Behavior of PVDF Nanocomposite by AC Dielectrophoresis Alignment of ZnO Nanowires. (15th October 2017) - Choi, Kyungwho; Choi, Woongchul; Yu, Choongho; Park, Yong Tae
Abstract : In contrast to commercial piezoelectric ceramics, lead-free materials such as ZnO and a polymer matrix are proper candidates for use in ecofriendly applications. In this article, the authors represent a technique using ZnO nanowires with a polyvinylidene fluoride (PVDF) matrix in a piezoelectric polymer composite. By aligning the nanowires in the matrix in a desired direction by AC dielectrophoresis, the piezoelectric behavior was enhanced. The dielectric constant of the composite was improved by increasing the concentration of the ZnO nanowires as well. Specifically, the resulting dielectric constant shows an improvement of 400% with aligned ZnO nanowires by increasing the poling effect compared to that of a randomly oriented nanowire composite without a poling process.